1996
DOI: 10.1021/bi9524272
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization of the Extracellular Domain of the Erythropoietin (EPO) Receptor by EPO:  One High-Affinity and One Low-Affinity Interaction

Abstract: Although there is considerable evidence that signaling by the erythropoietin (EPO) receptor is initiated when it is dimerized by binding EPO, it has been previously reported that the soluble extracellular domains of the EPO receptor (sEPOR) are not dimerized in the presence of EPO and are able to form only 1:1 complexes with EPO. We have now shown unambiguously by light scattering, sedimentation equilibrium, and titration calorimetry that two molecules of sEPOR can bind to a single EPO monomer but that the bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
134
1
2

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(144 citation statements)
references
References 35 publications
7
134
1
2
Order By: Relevance
“…Various mechanisms are employed for growth factor signaling upon interaction of each ligand with its receptor. These mechanisms include the 2: 1 receptorligand homodimer seen in the EPO and hGH systems (Cunningham et al, 1991;DeVos et al, 1992;Philo et al, 1996), the 2 1 receptor-ligand heterodimer complex seen for many cytokines including GM-CSF (Altman & Kastelein, 1995), and the 2:2 homodimer complex of interferon gamma with its receptor (Walter et al, 1995;Greenlund et al, 1996). We mutated surface-exposed residues on G-CSF to alanine in order to determine which regions of the four-helix bundle were important for receptor binding and activation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various mechanisms are employed for growth factor signaling upon interaction of each ligand with its receptor. These mechanisms include the 2: 1 receptorligand homodimer seen in the EPO and hGH systems (Cunningham et al, 1991;DeVos et al, 1992;Philo et al, 1996), the 2 1 receptor-ligand heterodimer complex seen for many cytokines including GM-CSF (Altman & Kastelein, 1995), and the 2:2 homodimer complex of interferon gamma with its receptor (Walter et al, 1995;Greenlund et al, 1996). We mutated surface-exposed residues on G-CSF to alanine in order to determine which regions of the four-helix bundle were important for receptor binding and activation.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the lack of self antagonism and the location of the receptor binding site suggest that a purely 2:1 receptorligand complex is unlikely to be the only active species. Hiraoka et al (1996) have shown that a single G-CSF molecule can form complexes with the extracellular domains of two receptor molecules, and other studies (Hiraoka et al, 1994;Philo et al, 1996) have suggested that 2:2 or even 4:4 ligand-receptor complexes may form at high ligand concentrations. Thus, studies to date are consistent with a receptor activation model whereby 2: 1 receptorligand complexes are formed at low concentrations of ligand and converted to 2:2 or higher order complexes at higher ligand concentrations.…”
Section: T" Lmentioning
confidence: 99%
See 1 more Smart Citation
“…The penalty term can be continuously made more stringent or be relaxed, even abandoned completely when the parameters have converged to a minimum with physically reasonable values (17). This method was used extensively for receptor-ligand interactions (29)(30)(31). Recently, the strategy to use the degree of violations of MC for selecting among alternative models for SE data was also used by Arkin and Lear in a separate post-fitting step (32).…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structure of the EPO-EPOR complex has been determined at a resolution of 1.9 Å [Protein Data Bank (PDB) ID code 1EER] (22). This structure demonstrates that Phe-48, Asn-147, Arg-143, and Arg-150 of EPO are among the key residues for binding to EPOR (20)(21)(22).We have taken the primary EPO-EPOR binding site as our target of protein-protein interface redesign. After scanning the PDB, rat pleckstrin homology (PH) domain of phospholipase C-␦1 (PLC␦ 1 -PH) was found to accommodate well the key interaction residues in EPO and at the same time can form a good interface with EPOR.…”
mentioning
confidence: 99%